2010
DOI: 10.1007/s10709-010-9486-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent evolution of molecular markers during laboratory adaptation in Drosophila subobscura

Abstract: The impact of genetic drift in population divergence can be elucidated using replicated laboratory experiments. In the present study we used microsatellite loci to study the genetic variability and differentiation of laboratory populations of Drosophila subobscura derived from a common ancestral natural population after 49 generations in the laboratory. We found substantial genetic variability in all our populations. The high levels of genetic variability, similar across replicated populations, suggest that ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
10
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 56 publications
5
10
0
1
Order By: Relevance
“…Although we assume that our laboratory populations represent the mitochondrial haplotypes of wild populations, there is a possible effect of homogenization as a result of our laboratory rearing (Berlocher and Friedman 1981;Simõ es et al 2008Simõ es et al , 2010. To avoid this, we collected a large number of individuals from wild populations that were used to establish the colonies, and the material for DNA extraction was obtained from the very Þrst generations in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Although we assume that our laboratory populations represent the mitochondrial haplotypes of wild populations, there is a possible effect of homogenization as a result of our laboratory rearing (Berlocher and Friedman 1981;Simõ es et al 2008Simõ es et al , 2010. To avoid this, we collected a large number of individuals from wild populations that were used to establish the colonies, and the material for DNA extraction was obtained from the very Þrst generations in culture.…”
Section: Discussionmentioning
confidence: 99%
“…Dlugosch & Parker () also saw this general tendency when compiling information on several founding events. Genetic drift due to reduced effective population size was the major force causing this loss of variability, and its effects changed through time, being stronger in the early phases of evolution after the founding event, reinforcing the conclusions of our previous studies (Simões et al ., , ). As expected, this effect was particularly strong for allelic richness (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…; Frankham ; Simoes et al . ). While effective population size is influenced by many factors, such as fluctuations in population size over generations, variation in family size and sex ratio, mating system and selection, work by Simoes et al .…”
Section: Discussionmentioning
confidence: 97%
“…While effective population size is influenced by many factors, such as fluctuations in population size over generations, variation in family size and sex ratio, mating system and selection, work by Simoes et al . () has shown that careful maintenance procedures can efficiently reduce the loss of genetic variability in laboratory populations in organisms that generate a high number of offspring. The results described here for the HVRx population corroborate this finding.…”
Section: Discussionmentioning
confidence: 99%